Evaluasi Penatausahaan Aset Tetap Pemerintah Kota Padang - Mustika, Rasyidah (Jurusan Akuntansi Politeknik Negeri Padang, 2015)
This research aims to evaluate the suitability of fixed assets on government administration of Padang city concerning the administration by Permendagri 17 on 2007 and the constraints of fixed assets in the administration of the Padang City. This research is a case study with a descriptive analysis techniques. Data collection techniques are by interview, observation and documentation. The evaluation is to evaluate the implementation of fixed asset accounting, fixed asset inventory, fixed asset reporting, and completeness of filling fixed asset documents.The result shown that the administration of fixed assets of Padang City have not achieve yet the degree of compliance in about 100%, because the average both evaluation of the accounting, inventory, reporting and completeness of the filling documents produced the degree of conformity in about by 62% or categorized as suitable category of Permendagri No. 17 on 2007. Un-maximum implementation of the government administration of Padang city is because there are many obstacles in the administration, such as limited data that support the fixed assets, socialization of the administration of the assets that is still weak, the limitation of human resources, and lack of adequate compensation for the welfare of employees in the field of assets administration.